2016
DOI: 10.1111/vco.12243
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective evaluation of lomustine (CeeNU) in 32 treatment naïve cats with intermediate to large cell gastrointestinal lymphoma (2006–2013)

Abstract: Multi-drug chemotherapy protocols for feline lymphoma have demonstrated variable efficacy and tolerability. In phase I trials, lomustine has demonstrated efficacy for cats with lymphoma though its use for treatment naïve feline intermediate/large cell gastrointestinal (GI) lymphoma remains unknown. This study evaluated the efficacy and tolerability of lomustine for the treatment of feline GI lymphoma. Thirty-two cats with histologically or cytologically confirmed intermediate/large cell GI lymphoma were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
56
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(66 citation statements)
references
References 29 publications
7
56
3
Order By: Relevance
“…The overall survival times in this study are comparable to those reported for cats with GI LSA treated with systemic chemotherapy alone . In addition to improving survival time, maintaining quality of life is an important goal in LSA case management because treatment is often palliative in nature.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…The overall survival times in this study are comparable to those reported for cats with GI LSA treated with systemic chemotherapy alone . In addition to improving survival time, maintaining quality of life is an important goal in LSA case management because treatment is often palliative in nature.…”
Section: Discussionsupporting
confidence: 71%
“…At initial examination, medical records indicated palpation of an abdominal mass in 30 cats. Complete blood counts were available for 34 cats, and the most commonly noted abnormalities were neutrophilia (11), anemia (11), leukocytosis (10), and monocytosis (4). Blood chemistry results were available for 29 cats, and the most commonly noted abnormalities were hyperglycemia (5), hypoalbuminemia (5), hyperglobulinemia (4), hypocalcemia (4), and low blood urea nitrogen (4).…”
Section: Demographicsmentioning
confidence: 99%
See 3 more Smart Citations